The craft of a good scribe history, narrative and meaning in the first tale of Setne Khaemwas - Vinson, Steve (Brill, 2018)
In 'The Craft of a Good Scribe', Steve Vinson offers a comprehensive study of the Demotic Egyptian 'First Tale of Setne Khaemwas' (Third Century BCE), the first to appear since 1900. "First Setne" is the most important extant Demotic literary text, and among the most important fictional compositions from any period of ancient Egypt. The tale, which is by turns lurid, tragic and ultimately comic, deals with Setne's theft a magic book written by the god Thoth himself, and subsequently Setne's punishment through a hallucinatory encounter with the ghostly femme fatale Tabubue.00Vinson provides a new textual edition and commentary, and explores the tale's cultural background, its modern reception, and approaches to its interpretation as a work of literature.0
Keywords: Setna-Roman 1; Setna-Roman